Constructing Adolescent Sexual Education in Algorithmic ‎Social Media Ecosystems: Family as a Socializing Agent - Rafi Maulana Ramadhan; Bintarsih Sekarningrum; Nunung Nurwati (Yayasan Darussalam Bengkulu, 2026)
This study aims to analyze the social construction of adolescent sexual education within algorithmic social media ecosystems and to examine the role of the family as a primary socialization agent in the context of a digital society. The study employs a Systematic Literature Review (SLR) approach guided by the PRISMA framework to identify, screen, and analyze reputable scholarly articles indexed in Scopus, Web of Science, ERIC, and SINTA published between 2019 and 2026. The study develops a comprehensive search strategy using combinations of keywords related to adolescent sexual education, algorithmic social media, and family socialization, and applies rigorous inclusion and exclusion criteria to ensure the relevance and quality of the selected studies. The findings indicate that adolescents predominantly obtain sexual information through algorithm-driven social media platforms such as Instagram, TikTok, and YouTube, which provide rapid, interactive, and personalized access to information. Algorithmic social media function not only as channels of information but also as emerging socialization agents that shape adolescents’ understanding, attitudes, and sexual behaviors. The study also reveals that the family continues to serve as a primary socialization agent by transmitting values, norms, and moral orientations through interpersonal communication, supervision, and the internalization of cultural and religious values. However, the findings highlight a dynamic contestation between parental authority and the power of algorithmic structures, which expand adolescents’ digital autonomy while constraining the effectiveness of parental control. The study concludes that the construction of adolescent sexual education is shaped through the interaction between algorithmic structures and family mediation. Therefore, families need to adopt dialogical, participatory, and digital literacy-based approaches to strengthen adolescents’ resilience in navigating sexual information within algorithmic social media environments.